Terrific tongues! - Gianferrari, Maria; Liu, Jia, (Illustrator) (Honesdale, Pennsylvania : Boyds Mills Press, an imprint of Highlights, 2018)
Provides facts about the different tongues in the animal kingdom and their unique abilities, from the sword-like tongue of the woodpecker that allows it to spear bugs under tree bark to the okapi, which can wash its face and ears with its tongue.
Keywords: Tongue -- Juvenile literature; Animals -- Adaptation -- Juvenile literature; Tongue; Animals -- Adaptation; Tongue; Adaptation (Biology)